MG53’s non-physiologic interaction with insulin receptor: lack of effect on insulin-stimulated Akt phosphorylation in muscle, heart and liver tissues - Lee, Kyung Eun; Nishi, Miyuki; Kim, Jongsoo; Murayama, Takashi; Dawson, Zachary; Wang, Xiaoliang; Zhou, Xinyu; Tan, Tao; Cai, Chuanxi; Takeshima, Hiroshi; Park, Ki Ho (Frontiers in Endocrinology, 2024)
Rationale: MG53's known function in facilitating tissue repair and anti-inflammation has broad applications to regenerative medicine. There is controversy regarding MG53's role in the development of type 2 diabetes mellitus.Objective: This study aims to address this controversy -whether MG53's myokine function contributes to inhibition of insulin signaling in muscle, heart, and liver tissues.We determined the binding affinity of the recombinant human MG53 (rhMG53) to the insulin receptor extracellular domain (IR-ECD) and found low affinity of interaction with Kd (>480 nM). Using cultured C2C12 myotubes and HepG2 cells, we found no effect of rhMG53 on insulin-stimulated Akt phosphorylation (p-Akt). We performed in vivo assay with C57BL/6J mice subjected to insulin stimulation (1 U/kg, intraperitoneal injection) and observed no effect of rhMG53 on insulin-stimulated p-Akt in muscle, heart and liver tissues.Overall, our data suggest that rhMG53 can bind to the IR-ECD, however has a low likelihood of a physiologic role, as the Kd for binding is ~10,000 higher than the physiologic level of MG53 present in the serum of rodents and humans (~10 pM). Our findings question the notion proposed by Xiao and colleagues -whether targeting circulating MG53 opens a new therapeutic avenue for type 2 diabetes mellitus and its complications.